Evaluasi Dan Monitoring Sebagai Instrumen Penguatan Strategi Pendidikan Islam - Halimah Halimah (GHIROH, 2025)
This study aims to analyze the implementation of evaluation and monitoring in the management of Islamic religious education learning. Evaluation is considered a regular stage to assess the effectiveness of planning, implementation, and achievement of Islamic education goals, while monitoring serves as a continuous monitoring tool to ensure that implementation is in accordance with established policies. This study uses a qualitative approach with a literature review method, while data are analyzed descriptively and analytically based on theory and previous research findings. The results show that learning evaluation includes various forms, including formative, summative, diagnostic, self-evaluation, joint formative evaluation, and portfolio evaluation. Educational monitoring emphasizes the importance of stakeholder involvement, strengthening the role of supervisors, and continuous monitoring of the quality of learning, curriculum, and teacher-student interactions.